Analisis Atraksi Wisata Dan Dampak Kebijakan Terhadap Masyarakat Sekitar Di Museum Konperensi Asia Afrika Bandung - Afifa Destiani, Jasmine; Ramdani, Dadan (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This study aims to analyze the tourist attractions at the Museum of the Asian-African Conference (MKAA) in Bandung and evaluate the impact of tourism budget allocation policies on educational, social, economic, and environmental aspects. The method used was descriptive qualitative, with data collection techniques through observation, in-depth interviews with visitors, MSMEs, and museum managers, and field documentation. The results indicate that the MKAA has succeeded in becoming an effective historical education platform, especially for school and university students. Socially, the museum raises public awareness of the importance of cultural heritage and enriches cross-cultural experiences for domestic and international tourists. The economic impact is also significant, with local business owners experiencing a 2-4 fold increase in income on weekends and holidays. Environmentally, conservation efforts have been made through the provision of green spaces and sanitation facilities, although challenges such as increased waste and traffic congestion remain. This study recommends the development of digital attractions, strengthening environmental management systems, and further studies using a quantitative approach to more comprehensively measure the effectiveness of the policy.